Runyoga: Från arisk blodsmystik till nyandlig självutveckling (Aura: Journal for the Study of New Religions, 2021)
Rune yoga is a spiritual practice based on the idea that the Runic alphabet can be used for spiritual and magical purposes. Based on an interpretation of the Runes where every letter in the alphabet is considered to contain within it a source of mystical powers Rune Yoga uses techniques inspired by Indian yoga to channel these forces. While contemporary Rune Yoga has become a part of Heathen and Alternative Spirituality that attracts people from a variety of Ethnic background the origin of the practice lies within the Ariosophical movement, a racial form of Esotericism that developed in Germany and Austria in the early 20th century. In this article the origin of Rune Yoga within the Ariosphical movement is presented, how it was integrated in ideas about Aryan racial supremacy. The article continues to show how Rune Yoga later migrated to North America and became a practice used within a non-racial milieu and what aspects remained from the original Ariosophical movement. The article argues that while some aspects of Ariosophical thinking remains within Rune Yoga the racial aspects have ceased to be important. Rather than focusing on race modern Rune Yoga focus in self-improvement for the individual and there is a lack of collectivist goals.